Estudo clínico e genético em portadoras de tecido mamário supranumerário - Nogaroto, Marli (1998)
The supernumerary breast tissue (SBT) can be characterised as polythelia or polymastia. Such abnormalities are relatively common in the general population and have caused much interest due to a possible association with alterations in the genitourinary and cardiovascular systems. In this study 53 women all carriers of SBT, were investigated. The group were studied in relation to the type, number, locality and familial inheritance. For the investigation of the associated anomalies, all of the patients were submitted to complimentary examinations, in particular, electrocardiogram (ECG), and pelvic and urinary tract ultrasound (US). For the purpose of comparing the results of the complementary examinations, a control group of 53 women without SBT, who had been submitted to ECG and US for different complaints, was included in the study. In the 53 patients, 74 SBT(s) were found. Polythelia was the most common type (60.38%) as opposed to polymastia (32.07%) and the presence of a combination of both in the same patient (7.55%). One type of SBT was by far the most frequently found (71.70%). In relation to the side, SBT was localised on the right in most of the cases, but its frequency was not statistically different to those localised on the left side. In the majority of patients (94.59%) SBT was located along the milk line. As far as the atypical site, two presented SBT in the scapular region, one in the dorsal region and the other on the thigh. These results are compatible with the others previously published in the literature. In 41.51% of the cases studied a family history was observed, the greatest frequency that had been related before was 11.64%. Such a difference is statistically significant. Therefore the number of family cases described must have been underestimated due to the difficulty in identifying SBT because it is easily hidden by clothes and because it is confused with other alterations, among which nevus, scars and neurofibroma. The inheritance is consistent for SBT and recognised as autosomal dominant with variable expressivity. In the studied sample, however, dominant inheritance linked to the X gene and an incomplete penetrance can not be discarded. Therefore, it can be suggested that the genetic etiology of SBT involves different mutations with different patterns of inheritance. The symptoms in relation to SBT, referred by the patients, were compatible with those previously published and included pain, increase in size and lacteal secretion. The frequency of the observed alterations in the ECG of the group of patients with SBT and of the control group did not show a statistical difference. However, the data of US showed a significant difference between the two groups (patients with SBT 32.08% and the control group 16.98%). However, according to what has already been proposed by a series of authors in the SBT presence the physician must be attentive to the occurrence of nephrourinary defects, mainly to diagnose or prevent complications which may include malignant neoplasies.